General conditions and main problems of implementing the Basel III international standards for the banking system of Kazakhstan - Болат, А. (Journal of Economic Research & Business Administration, 2017)
Based on the lessons of the financial crisis of 2008-2009, the Basel Committee of Banking Supervision launched a revision of its requirements on capital sufficiency. In this connection, Basel III document was adopted by the Basel committee of banking supervision. Currently, the community is having many questions about the standards and their application, the timing of the introduction of Basel 3, the possible consequences of these changes. Therefore, this leads to the relevance of this research.The paper considers the approaches of the National Bank of the Republic of Kazakhstan toward the capital adequacy requirements and conservation buffer for the second-tier banks in the process of upcoming reform of banking regulation and international settlement known as “Basel-III”. Basic provisions of Basel III as well as the principles of integration of the country’s banking system to the Basel agreement are discussed. In particular, the author focuses on such principles as tightening of capital adequacy requirements, establishment of single liquidity standards, and additional standards for the global systematically important financial institutions. The paper provides an overview of possible impact that Basel III standards might exert on the banking system operation, economic growth and financial stability. Further, the author conducts a comparative analysis of capital adequacy requirements and conservation buffer established by the regulators in such countries as Kazakhstan, Russia, and Singapore.